Pengaruh Cash Turnover, Current Ratio, dan Debt to Equity Ratio Terhadap Profitabilitas Pada Perusahaan Properti yang Terdaftar di Bursa Efek Indonesia - Ni Putu Erika Susanti; A.A. Ketut Jayawarsa; Kadek Goldina Puteri Dewi (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2024)
The purpose of this study is to determine the effect of cash turnover, current ratio and debt to equity ratio on profitability conducted in property companies listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling, so the samples in this study were 78 samples. The data analysis technique used is multiple linear regression. The results showed that Cash Turnover had no effect on Return On Assets in Property Companies Listed on the Indonesia Stock Exchange. This indicates that the increase in Cash Turnover cannot affect the increase in Return On Assets in Property Companies Listed on the Indonesia Stock Exchange. Current Ratio has a positive effect on Return On Assets in Property Companies Listed on the Indonesia Stock Exchange. This indicates that an increase. in the Current Ratio can affect the increase in Return On Assets in Property Companies Listed on the Indonesia Stock Exchange. Debt to Equity Ratio does not affect Return On Assets in Property Companies Listed on the Indonesia Stock Exchange. This indicates that an increase in the Debt to Equity Ratio cannot affect the increase in Return On Assets in Property Companies Listed on the Indonesia Stock Exchange